(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
CoViD-19 is producing a number of changes in the meaning of health. In order to protect our health, States have restricted the exercise of many rights: movement, education, work, etc.Â Health has thus become a tyrant that crushes all other rights. On the other hand, shortages impose choices for access to intensive care beds, leading to a tragic selection between those who can be treated and those who cannot. In this way, CoViD-19 has denied the health of the excluded. Finally, the pandemic has revealed a condition of great inequality in access to treatment. The article examines these dynamics within a framework of constitutional principles in order to draw lessons for the possible emergence of new pandemics.